2014
DOI: 10.1186/s12918-014-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the quantitative balance between insulin-like growth factor (IGF)-1 ligand, receptor, and binding protein levels to predict cell sensitivity and therapeutic efficacy

Abstract: BackgroundThe insulin-like growth factor (IGF) system impacts cell proliferation and is highly activated in ovarian cancer. While an attractive therapeutic target, the IGF system is complex with two receptors (IGF1R, IGF2R), two ligands (IGF1, IGF2), and at least six high affinity IGF-binding proteins (IGFBPs) that regulate the bioavailability of IGF ligands. We hypothesized that a quantitative balance between these different network components regulated cell response.ResultsOVCAR5, an immortalized ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…It is possible that variations in the levels of other components of the cellular signaling network besides growth factor receptors could be responsible for the observed heterogeneity. For example, it has been shown that when predicting cell response, dimerization patterns of ErbB1 with other ErbB receptors is important to consider [ 60 ], as is the ratio of IGF1 to IGF1R and the level of the IGF binding proteins [ 61 ]. Likewise, previous work from our lab demonstrated that it was necessary to incorporate the levels of both ligands and receptors when predicting ovarian cancer cell response to an ErbB-targeted inhibitor [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that variations in the levels of other components of the cellular signaling network besides growth factor receptors could be responsible for the observed heterogeneity. For example, it has been shown that when predicting cell response, dimerization patterns of ErbB1 with other ErbB receptors is important to consider [ 60 ], as is the ratio of IGF1 to IGF1R and the level of the IGF binding proteins [ 61 ]. Likewise, previous work from our lab demonstrated that it was necessary to incorporate the levels of both ligands and receptors when predicting ovarian cancer cell response to an ErbB-targeted inhibitor [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing number and sophistication of the models, these studies have not considered insulin signaling. Conversely, computational models of insulin signaling exist [ 42 , 43 ], but have only been applied to other applications, including articular cartilage [ 44 ], ovarian cancer [ 45 ], and human skeletal muscle [ 46 ], and exclude molecules of interest for brain cancer cells [ 44 , 47 ]. Thus, we created for the first time, a computational chemical-kinetic model linking the insulin signaling pathway to glioblastoma growth.…”
Section: Introductionmentioning
confidence: 99%
“…e activities of IGF-1 are controlled by interaction of several high-a nity IGFBPs; especially IGFBP3 which directly carries IGF-1 to target tissues, prevents it from proteolytic degradation and regulates its interaction with IGF-1R. Its expression is negatively related to IGF-1 expression [17,18]. IGF1 and IGFBP3 gene polymorphisms may a ect circulation levels of IGF1 and IGFBP3, and high IGF1 level but low IGFBP3 level contributes to increased cancer risk [7,19].…”
mentioning
confidence: 99%